PENGGUNAAN EUFEMISME DALAM TEKS BERITA COVID-19 HARIAN FAJAR MAKASSAR - Ambarwati, Lia Novela; Mayong, Mayong; Idawati, Idawati (Universitas Negeri Makassar, 2024)
This study aims to (1) describe the forms of euphemism in the COVID-19 news articles of Harian Fajar Makassar; and (2) describe the functions of euphemism in the COVID-19 news articles of Harian Fajar Makassar. The data for this research consists of excerpts from news texts in the form of words, phrases, clauses, and sentences containing euphemisms in the COVID-19 news articles of Harian Fajar Makassar. The data collection techniques used are the listening technique, the note-taking technique, and the documentation technique. Data analysis is carried out by analyzing the data, presenting the data, and drawing conclusions. The results of the study show that (1) the forms of euphemism found in the COVID-19 news articles of Harian Fajar Makassar include abbreviations, loanwords, foreign terms, periphrasis, and metaphors. (2) The functions of euphemism found in the COVID-19 news articles of Harian Fajar Makassar include functions of politeness and comfort, functions of meaning concealment, the religious term function